Prevalence and correlates of multimorbidity among individuals aged 50 and above in Bangladesh - Faroque Md Mohsin; Padam Kanta Dahal; Md. Badsha Alam; Sarah Tahera Mahmud; Cotton Chakma; Md. Iqbal Hossain; Md. Atikur Rahman Akanda; Maherun Nesa; Rajib Kumar Malakar; Sokal Roy; Shahriar Hasan; Nitai Roy (Discover Public Health)
Abstract Objectives This study assessed the prevalence and factors associated with multimorbidity among adults in community settings in Bangladesh. Methods A cross-sectional study was conducted among 600 individuals aged ≥ 50 years living in three districts of Bangladesh. A multi-stage cluster sampling technique was used. Data were collected through structured interviews covering individual-level, household-level, and community-level factors. The presence of multimorbidity was determined based on self-reporting of two or more known diagnoses of chronic conditions. Logistic regression was used to assess the factors associated with multimorbidity. Results The prevalence of multimorbidity among individuals was around 39% (95% CI: 34.6–42.4), with hypertension (35%) being the most common condition. Being unemployed, having a smaller family size, and a lower monthly income were significantly associated with higher odds of multimorbidity, with odds ratios of 1.78 (95% CI: 1.02–3.10), 1.49 (95% CI: 1.04–2.13), and 1.72 (95% CI: 1.11–2.68), respectively. Conclusions We found a 39% prevalence of multimorbidity among older adults in Bangladesh, having hypertension as the most prevalent condition. Our findings may help to emphasize the importance of providing awareness-building programs and increasing investment in healthcare services to provide services for decreasing multimorbity